CROSS-CULTURAL DIFFERENCES PECULIARITIES OF THE INTERDEPENDENCE OF REGULATORY PROCESSES AND ADAPTATION OF STUDENTS TO THE CONDITIONS OF TRAINING IN THE UNIVERSITY - Tatiana Banshchikova; Varvara Morosanova (Вестник Северо-Кавказского федерального университета)
The article presents the main results of the study of the relationship between self-regulation and the adaptation to the training group and the educational activities of Russian students, students from distant and near abroad. At the first stage of the study, the peculiarities of the students' adaptation to the conditions of study at the university were established, and the second one explored the peculiarities of regulatory processes among respondents belonging to different cultural communities. At the third stage, a search was made for possible links between the main indicators of adaptation and the indicators of conscious self-regulation. It was established that the ethnos culture and regional features, represented in traditions and customs, set the basic vector and standards ofsubjective evaluation of the importance of the social space of the individual. In the study of the problem of self-regulation in the situation of adaptation to a new socio-cultural environment new facts are established: self-regulation is one of the essential factors in the situation of students' adaptation to a new training group and educational activity.